2020
DOI: 10.1111/cico.12427
|View full text |Cite
|
Sign up to set email alerts
|

When Heritage Meets Creativity: A Tale of Two Urban Development Strategies in Kampong Glam, Singapore

Abstract: In recent years, cities around the world have increasingly relied on culture‐based development strategies for the revitalization of urban areas, such as urban heritage and the development of a creative economy. Typically, either one of these practices is put in place; however, in Kampong Glam, Singapore, both heritage development and creative economy strategies have been adopted by the national government and local organizations. This paper studies the coincidence of the two main culture‐based urban developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Shortly thereafter, cultural/creative cities began to diffuse as a "universal policy" and "best practice" to Asian countries such as Singapore, South Korea, and China, becoming a key strategy for these emerging markets to build global cities and actively integrate into the global economy (Kim 2017:314;Lin and Chiu 2019:320;Oakes and Wang 2016:1). In Singapore, for example, the creative economy has been effective in promoting urban development by combining it with heritage conservation (Kumar 2020). In pre-reform China, culture mainly served revolutionary politics.…”
Section: State-led Cultural and Creative Industries In Asian Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly thereafter, cultural/creative cities began to diffuse as a "universal policy" and "best practice" to Asian countries such as Singapore, South Korea, and China, becoming a key strategy for these emerging markets to build global cities and actively integrate into the global economy (Kim 2017:314;Lin and Chiu 2019:320;Oakes and Wang 2016:1). In Singapore, for example, the creative economy has been effective in promoting urban development by combining it with heritage conservation (Kumar 2020). In pre-reform China, culture mainly served revolutionary politics.…”
Section: State-led Cultural and Creative Industries In Asian Citiesmentioning
confidence: 99%
“…In Singapore, for example, the creative economy has been effective in promoting urban development by combining it with heritage conservation (Kumar 2020). In pre-reform China, culture mainly served revolutionary politics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…State institutions and local stakeholders encourage diversity of occupants and usage. Having learnt from past mistakes, they prevented it from becoming an exclusive tourist hub that has no relevance to the resident population (Kumar, 2020). The emergence of a mixed cluster typology in the northern part of the district promises a neighborhood steeped in culture and diversity.…”
Section: Case Studiesmentioning
confidence: 99%
“…For example, a degree of comfort and attraction involving a place may affect users’ physical or emotional responses. Creative approaches potentially stigmatized and displaced disadvantaged groups, such as the poor, racial-ethnic minorities, the elderly and individuals with disabilities (Kumar, 2020). Lyons (1983) indicated that demographic and social factors could significantly influence the definition of user preferences toward a specific environment.…”
Section: Placing Urban Design Into the Creative Placemaking Modementioning
confidence: 99%